SOCIOEPIDEMIOLOGICAL STATUS AND CLINICAL OUTCOME OF MDR-TUBERCULOSIS PATIENTS AT KING GEORGE’S MEDICAL UNIVERSITY, LUCKNOW (International Journal of Food and Nutritional Sciences, 2022)
Tuberculosis is a major global health concern. It causes ill-health among millions of people each year and remains a leading cause of morbidity and mortality in developing countries. The prevalence of drug resistant tuberculosis is rapidly emerging worldwide.The complex nature of MDR TB necessitates innovative strategies and urgent interventions to curb its spread and improve treatment outcomes. MDR TB is a serious health problem worldwide that poses a major challenge to TB control efforts worldwide. It is evaluated that there were 484,000 active cases of MDR TB worldwide in year 2020, with the very heavy burden of disease in developing nations such as India, China, and the Russian. MDR TB is particularly concerning because it requires longer and more complicated treatment regimens that are associated with greater rate of disruption of medical treatment, which ultimate result in relapse, and death. The emergence of MDR TB is largely attributed to incomplete or improper treatment of TB, which can cause in the development of drug-resistant variant of M. tuberculosis. This can occur when active case patients do not have their drugs on time or as prescribed by the doctor and this cause the medical treatment to be incomplete on time or have lower or bad quality of medicine which are not as effective as it have to be against the bacteria.